Exploring the Impact of Group-Based Psychodrama Techniques on Reducing Hostility in Adolescents (Journal of Academic Research, 2025)
AbstractThis study aims to examine the effectiveness of group-based Psychodrama sessions in reducing hostile behaviors among young adolescents in Libya. Employing a mixed-methods approach, both quantitative and qualitative data were collected through purposive sampling. For the quantitative aspect, a survey was conducted to assess aggression levels in adolescents from 10 preparatory schools in Misurata, with a sample of 350 students aged 13 to 15. These students were selected by school counselors based on two criteria: a history of high aggression and a willingness to participate. In the experimental phase, 66 students from one school were split into two groups: the experimental group (33 students) and the control group (33 students). The results revealed a significant decrease in hostility and a notable improvement in problem-solving abilities among students in the experimental group, as indicated by the mean score differences when compared to the control group.